Study of Characteristics of Fault Slip and Induced Seismicity during Hydraulic Fracturing in HDR Geothermal Exploitation in the Yishu Fault Zone in China. (7th April 2021) - Niu, Zhiyong; Wang, Shiquan; Ma, Hongrui; Luan, Hengjie; Ding, Zhouyuyan
Abstract : Hot dry rock (HDR) geothermal energy has become promising resources for relieving the energy crisis and global warming. The exploitation of HDR geothermal energy usually needs an enhanced geothermal system (EGS) with artificial fracture networks by hydraulic fracturing. Fault reactivation and seismicity induced by hydraulic fracturing raise a great challenge. In this paper, we investigated the characteristics of fault slip and seismicity by numerical simulation. The study was based on a hydraulic fracturing project in the geothermal field of Yishu fault zone in China. It revealed that fluid injection during hydraulic fracturing can cause the faults that exist beyond the fluid-pressurized region to slip and can even induce large seismic event. It was easier to cause felt earthquakes when hydraulic fracturing was carried out in different layers simultaneously. We also examined the effects of the location, permeability, and area of the fracturing region on fault slip and magnitude of the resulting events. The results of the study can provide some useful references for establishing HDR EGS in Yishu fault zone.